KEPASTIAN HUKUM HAK NORMATIF PEKERJA BERUPA UANG PISAH PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2023 - Azani, Adila; Elvionita, Septiara; Nurfitrah, Mesya Assauma (Solusi, 2025)
The regulation concerning severance pay was previously governed by Article 158 paragraph (4), Article 164 paragraph (2), and Article 168 paragraph (3) of the Manpower Law. These three articles were removed following the enactment of Law Number 11 of 2020 on Job Creation and Law Number 6 of 2023 on the Ratification of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law. However, provisions on severance pay are still found in Government Regulation Number 35 of 2021 on Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Periods, and Termination of Employment, which serves as the implementing regulation of Law Number 11 of 2020 on Job Creation. This situation creates confusion in its implementation and may potentially lead to a gap in the protection of workers' normative rights by employers. The problem addressed in this paper is how the legal certainty of workers' normative rights in the form of severance pay is post the enactment of Law Number 6 of 2023. This research is a juridical-normative study with a descriptive-analytical approach. The result of this study shows that Government Regulation Number 35 of 2021 is still in effect as one of the positive labor laws, even though the provisions of Article 158 paragraph (4), Article 164 paragraph (2), and Article 168 paragraph (3) were abolished with the enactment of Law Number 6 of 2023, because the basis for the enactment of Government Regulation Number 35 of 2021 is the provisions of Article 81 and Article 185 letter b of the Job Creation Law, which were not abolished by the enactment of Law Number 6 of 2023. This means that the right to severance pay, as one of the workers' normative rights, must still be fulfilled by employers as part of their obligations when a termination of employment occurs, according to the criteria set out in these articles that result in the entitlement to severance pay.